2017
DOI: 10.1111/1462-2920.13642
|View full text |Cite
|
Sign up to set email alerts
|

It is elemental: soil nutrient stoichiometry drives bacterial diversity

Abstract: SummaryIt is well established that resource quantity and elemental stoichiometry play major roles in shaping below and aboveground plant biodiversity, but their importance for shaping microbial diversity in soil remains unclear. Here, we used statistical modeling on a regional database covering 179 locations and six ecosystem types across Scotland to evaluate the roles of total carbon (C), nitrogen (N) and phosphorus (P) availabilities and ratios, together with land use, climate and biotic and abiotic factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
160
5
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(188 citation statements)
references
References 40 publications
21
160
5
2
Order By: Relevance
“…Our study provides novel insights into the cross‐biome vulnerabilities, ecological preferences and diversity hotspots of dominant soil invertebrate taxa. Unlike bacterial diversity, which responds most strongly to changes in soils (Bastida et al, ; Delgado‐Baquerizo, Reich, et al, ), we found that climate and plant attributes regulated the diversity of nematodes, arachnids and rotifers, suggesting that these organisms might be more vulnerable directly by changes in climate, or indirectly, by changes in plant communities. For example, our study provides evidence that reductions in forest cover and plant diversity, and declines in plant production associated with increases in aridity might have negative consequences for the diversity and dominant taxa of invertebrates globally.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Our study provides novel insights into the cross‐biome vulnerabilities, ecological preferences and diversity hotspots of dominant soil invertebrate taxa. Unlike bacterial diversity, which responds most strongly to changes in soils (Bastida et al, ; Delgado‐Baquerizo, Reich, et al, ), we found that climate and plant attributes regulated the diversity of nematodes, arachnids and rotifers, suggesting that these organisms might be more vulnerable directly by changes in climate, or indirectly, by changes in plant communities. For example, our study provides evidence that reductions in forest cover and plant diversity, and declines in plant production associated with increases in aridity might have negative consequences for the diversity and dominant taxa of invertebrates globally.…”
Section: Discussioncontrasting
confidence: 45%
“…Our study provides novel insights into the cross-biome vulnerabilities, ecological preferences and diversity hotspots of dominant soil invertebrate taxa. Unlike bacterial diversity, which responds most strongly to changes in soils (Bastida et al, 2016;Delgado-Baquerizo, Reich, et al, 2017), we found that climate and plant attributes regulated the diversity of nematodes, arachnids and rotifers, suggesting that these organisms might be more vulnerable directly by changes in climate, or indirectly, by changes in plant communities.…”
Section: Discussionmentioning
confidence: 62%
“…For example, the typically negative relationships between N:P ratios and the diversities of zoo-and phytoplankton (He et al, 2013) are associated with the shortened pathways and lower transfer rates of matter and energy along trophic webs under P limitation (Elser et al, 2000). Nutrient limitation and high N:P ratios are consistently associated with shifts from fast-to slow-growing species in all types of media (Busch et al, 2018;Penuelas et al, 2013), and soil microbial and decomposer faunal compositions are consistently associated with soil and litter N:P ratios (Barantal, Schimann, Fromin, & Hättenschwiler, 2014;Delgado-Baquerizo et al, 2017;Eo & Park, 2016;Lee et al, 2015Lee et al, , 2017Leflaive et al, 2008;Ren et al, 2017;Su et al, 2015).…”
Section: Aquatic Ecosystemsmentioning
confidence: 99%
“…The shifts in organisms' N:P ratio resulting from different environmental conditions are strongly related with shifts in ecosystems structure and function (Loladze & Elser, 2011;Penuelas et al, 2013;Sterner & Elser, 2002). Imbalances between these two nutrients, N and P in natural, seminatural, and managed ecosystems (Carnicer et al, 2015;Delgado-Baquerizo et al, 2017;Hu et al, 2018;Liu, Fu, Zheng, & Liu, 2010;Penuelas et al, 2013;Ulm, Hellmann, Cruz, & Máguas, 2016), reduce C capture and global Isles, Creed, & Bergstrom, 2018). Atmospheric P deposition is also increasing due to the rising levels of anthropogenic emissions of P to the atmosphere (3.5 Tg P/year), which have led to current net continental and oceanic rates of P deposition of 2.7 and 0.8 Tg P/year, respectively (Wang, Balkanski, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The more suitable the temperature and precipitation condition, the more litter fall accumulation above soils. Climatic variables also have an impact on microbial activities, which are of vital importance for the decomposition of organic matter (Cleveland and Liptzin, 2007;Delgado-Baquerizo et al, 2017). To date, the most used dataset of climatic variables in ecological modeling consists largely of annual trends (e.g., MAT and MAP), seasonality (e.g., annual range of temperature and precipitation) and extreme or limiting conditions (e.g., TTQ, TWM) of temperature and precipitation.…”
Section: Predictor Selectionmentioning
confidence: 99%